Novel Cd(II) Ion Imprinted Polymer Coated on Multiwall Carbon Nanotubes as a Highly Selective Sorbent for Cadmium Determination in Food Samples. (27th November 2019) - Aboufazeli, Forouzan; Zhad, Hamid Reza Lotfi Zadeh; Sadeghi, Omid; Karimi, Mohammad; Najafi, Ezzatollah
Abstract: The application of a novel Cd(II) ion imprinted polymer coated on multiwall carbon nanotubes was investigated for preconcentration and determination of low levels of Cd ions. This novel sorbentwas characterized by scanning electron microscopy, thermal gravimetric/differential thermal analysis, elemental analysis, and FTIR spectrometry. Effects of various factors, such as pH of the sample solution, eluent (type, concentration, and volume), and flow rates of the sample and eluent, were evaluated in this study. To investigate the selectivity of the sorbent toward Cd(II) ions, the effects of a variety of ions on preconcentration and recovery of Cd(II) ions were investigated. TheLOD was 1.3 ng/mL; the recovery and RSD of the method were 96.4% and below 3.1%, respectively. Validation of the method was performed by analyzing some standard reference materials with certified Cd(II) concentrations. Finally, the sorbent was applied for separation and determination of Cd(II)ions in food samples.